The Types of Impoliteness in â€œInside Outâ€ The Movie - Muchamad Daffa; Mhd Johan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study uses a pragmatic study to observe types of impoliteness based on the film "Inside Out". The purpose of this research is to find out the types of impoliteness used by the characters in the movie "inside out". then, the researcher used the theory from Culpeper (2011)to analyze the data. the data source was found from the speakers and hearers in the movie "inside out". to provide research results, researchers used a research design in the form of descriptive qualitative. The research design used by researchers comes from Creswell (2009). for data collection, researchers used the observational method by Sudaryanto (2015). data collection techniques carried out by researchers, namely, first the researcher watched the film "inside out". second, the researcher reads the transcript and looks at the context to be analyzed. third, the researcher finally found the types of impoliteness that occur between the characters in the movie "inside out". Thus, the researcher can find 13 utterances that contain types of impoliteness. utterances that contain types of impoliteness are used by speakers and listeners in the film "inside out", with the discovery of 8 forms of coercive impoliteness, affective impoliteness, and entertaining impoliteness.